2011
DOI: 10.1111/j.1365-2591.2011.01860.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of several digital radiographic imaging systems for laboratory determination of endodontic file length

Abstract: The three digital radiographic imaging systems were precise. The CDR Wireless system was significantly more accurate in determining endodontic file lengths, and similarly to Digora Optime, was considered the least difficult to use when assessing endodontic file lengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…10 Despite the high resolution and great image quality presented by current digital images, it is important to check if they allow better accuracy and precision on different tasks. 11 Several studies have evaluated the ability of CBCT in measuring the dental arch and surrounding structures. 1,2,4,5,8,9 Mullen et al 5 and Luu et al 12 demonstrated that CBCT is as accurate as DPM in the attainment of measurements, which is in agreement with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…10 Despite the high resolution and great image quality presented by current digital images, it is important to check if they allow better accuracy and precision on different tasks. 11 Several studies have evaluated the ability of CBCT in measuring the dental arch and surrounding structures. 1,2,4,5,8,9 Mullen et al 5 and Luu et al 12 demonstrated that CBCT is as accurate as DPM in the attainment of measurements, which is in agreement with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoral solid‐state sensors have been tested in different settings. Nonetheless, such studies tested a small number of sensors that generated images which were evaluated by a relatively small number of clinicians. This study has greater validity than previous studies, all of which used fewer types of sensors, fewer evaluators or both.…”
Section: Discussionmentioning
confidence: 98%
“…Studies determining file lengths in the root canal have been performed previously (6,7,14,16). This measurement does not address the exact clinical procedure during an endodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, endodontic files were introduced in the root canal according to the method proposed by Ingle (15). Tooth length was obtained from a previous study (7) in which, after an initial film-based radiograph, the distance between the incisal border and the apical root was measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation